2009
DOI: 10.1259/bjr/28241773
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial delayed enhancement in patients with pulmonary hypertension and right ventricular failure: evaluation by cardiac MRI

Abstract: In this study, we evaluated patients with pulmonary arterial hypertension (PAH) and impaired right ventricular function. We used cardiac MRI for the detection of myocardial delayed enhancement (MDE) and its possible association with other clinical variables. 20 patients (6 males and 14 females, aged 44.5+/-11 years; 15 New York Heart Association class III, 5 class IV) with known PAH (13 idiopathic, 7 resulting from chronic pulmonary embolism) were evaluated for the detection of MDE. Short-axis cine images of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Blyth et al 11 noticed the presence of DME on 23 of 25 study patients, of 3.3g and there was a positive correlation with several hemodynamic variables, primarily patients with paradoxical interventricular septum deviation. Junqueira et al 26 demonstrated the presence of DME in 65% of study patients and only found a positive correlation with the duration of the disease at diagnosis.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Blyth et al 11 noticed the presence of DME on 23 of 25 study patients, of 3.3g and there was a positive correlation with several hemodynamic variables, primarily patients with paradoxical interventricular septum deviation. Junqueira et al 26 demonstrated the presence of DME in 65% of study patients and only found a positive correlation with the duration of the disease at diagnosis.…”
Section: Discussionmentioning
confidence: 87%
“…Even though there are several studies of DME evaluated by CMR in conditions that affect the LV, only three of major importance evaluated this finding in patients with PAH 11,25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, unlike Blythe et al and Sanz et al, they did not find a significant correlation between the extent of LGE and hemodynamic parameters of PH, despite the fact that their cohort of patients had a higher overall mPAP when compared to the study by Blyth et al (54 ± 16 mmHg vs. 43 ± 12 mmHg) and Sanz et al (54 ± 16 mmHg vs. 44 ± 12). The most recent study examining RVIP-LGE in patients with PH showed RVIP-LGE in only 13/20 patients and the only significant correlation was found between the extent of LGE and the duration of disease and not with RV size, function, or hemodynamics [10]. Our study is in agreement with the findings by Blyth et al and Sanz et al but builds on the relatively small amount of data available on this topic by including more patients and additionally following them over time.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also reported the presence of LGE in the right ventricular insertion point (RVIP) at the inter-ventricular septum (between the RV and LV) of patients with PAH. Results suggest a significant inverse correlation between the degree of RVIP-LGE and RVEF and haemodynamics [41][42][43][44]. Recently, RVIP-LGE has been shown to be associated with RV dilation and hypertrophy, reduced RVEF and more extensive haemodynamic abnormalities, as well as a univariate predictor of time to clinical worsening ( fig.…”
Section: Beyond Conventional Cmrimentioning
confidence: 93%